2004
DOI: 10.4049/jimmunol.172.8.4844
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Cellular and Humoral Immune Response against Mutated p53 in a Patient with Lung Cancer

Abstract: We recently identified several Ags recognized by tumor-infiltrating B lymphocyte-derived Ab using SCID mice and a xenografted non-small cell lung cancer system. One of these identified Ags was mutated p53 with a point mutation resulting in the alteration of codon 158 from Arg to Leu. The aim of this study was to ascertain whether cellular immunity against mutated p53 exists in the same patient together with humoral immunity. Two different nona peptides (mutated p53150 and p53155 peptides), including a mutated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 29 publications
(32 reference statements)
0
59
0
Order By: Relevance
“…To generate T-cell clones, limiting dilution was done from the bulk CTL line 7 days after the last stimulation as previously described (14). The cells were seeded at 0.1, 0.3, 1, or 3 per well in 96-well round-bottomed plates and stimulated under the following culture condition: culture medium with irradiated F1121L cells and Rosi EBV-B cells as a feeder in the presence of IL-2 (100 units/mL), IL-4 (5 ng/mL), and IL-7 (5 ng/mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To generate T-cell clones, limiting dilution was done from the bulk CTL line 7 days after the last stimulation as previously described (14). The cells were seeded at 0.1, 0.3, 1, or 3 per well in 96-well round-bottomed plates and stimulated under the following culture condition: culture medium with irradiated F1121L cells and Rosi EBV-B cells as a feeder in the presence of IL-2 (100 units/mL), IL-4 (5 ng/mL), and IL-7 (5 ng/mL).…”
Section: Methodsmentioning
confidence: 99%
“…2B). The mutated p53 peptide (TRVLAMAIY), which has been identified as a tumor antigen restricted by HLA-Cw*0702 (14), was used as a negative control.…”
Section: Cancer Researchmentioning
confidence: 99%
“…33,34 In many instances, anti-p53 antibody responses have been shown to decrease following surgical intervention. Interestingly, the A904L lung cancer cell line was initially characterized as accumulating p53 molecules using antibodies derived from the autologous patient's B cells, 26 which suggests that a Th2-biased anti-p53 immune response might have blocked/ reduced the CTL response against this mutant epitope. Interestingly, unlike most p53 sero-positive patients, the A904 patient was reported to have survived at least 6 years following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown to be naturally presented in association with HLA-Cw*0702 molecules using CTL induced/expanded from lymphocytes obtained from the autologous A904 patient. 26 These mutated p53 antigens, which are ''non-self'' and the equivalent of the highly restricted, tumor rejection antigens of murine tumors, such as the Meth A p53 mutant antigen, should induce potent antitumor immunity. 3,27 In general, mice can be readily protected from lethal tumor challenges by prior immunization with irradiated tumor or sub-lethal doses of viable tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies on immunotherapy indicated favorable therapeutic effects, and suggested that such a strategy might represent an alternative treatment approach for lung cancer (2,3). A large number of tumor-associated antigens have been identified in various human cancers (4)(5)(6). A high level of CD8 T cell infiltration into tumor tissues has been reported to be associated with a better prognosis in colon carcinoma and in ovarian cancer, suggesting that antitumor immunity can be provoked in cancer patients (7,8).…”
Section: Introductionmentioning
confidence: 99%